Parainfectious Optic Neuritis Followed by Microcystic Macular Oedema - Hipólito-Fernandes, D (2019)
Parainfectious optic neuritis is a very rare cause of acute vision loss. We present a case of a 51-year-old man with a recent upper respiratory tract infection, presumably of viral aetiology, who showed up with complains of painless right eye vision loss, followed by the same symptoms on the left eye 3 weeks later. Ophthalmological examination revealed optic disc swelling (sequential in severity) which was confirmed by optic disc imaging. The remaining evaluations (lumbar puncture, MRI, laboratory and genetic testing) were completely normal. Considering a postviral aetiology, 5-day intravenous methylprednisolone treatment was performed. Follow-up examinations revealed slight visual acuity and visual fields recovery, with subsequent optic disc atrophy and microcystic macular oedema, bilaterally. This case illustrates how important a correct clinical history is to guide a correct diagnosis and posterior management.